Pesquisa fenomenológica na justiça do trabalho : proposta de uma concoliação humanista - Sousa, Nayara Queiroz Mota de (2010)
The Judiciary has exercised a great influence on the formation of the Brazilian state, which emphasized the role of the judicial profession in society. As jurists, the judges had a great influence in developing the structure and the state organization that earned them enormous prestige and power within the social environment. This feature associated with the struggle for independence and professionalism of the category generated a distance of judges with the public, and training for the judges based on the Cartesian method of doing science, which not accompanied the social changes brought by modernity, has enlarged this distance, generating a dissatisfaction with the performance of the Judiciary, including the labor sector. The increased conflictuality that caused by the changes implemented in the modern world requires rapid and effective responses of the judiciary, social as peacemaker. In this scenario, the means of conflict resolution should be privileged, that beyond the Judiciary of relief, resolve the dispute within society. Reconciliation has been promoted as the best and quickest solution to the lawsuits, so they need to be improved. Humanizing is an alternative approach to the judiciary of the citizen and helping in the mission of pacifying the conflict, for it promises the improvement of the person to cope better in society, in a time when the isolation and the contradictions seem to reach the modern man. This study aimed to identify the direction of the relationship between the judge and the parties, through an existential phenomenological research, using as a methodological tool, the version of meaning, to collect data. Results and discussion show that the speech of judges and parties of the axes of meanings emerged that reveal the feelings of each search, including specific thematizations Judges; axes that are communicated in the experiences of the parties and others axes which are peculiar to each part in particular. Analyzing these units of meaning they can trace connections to the literature review, highlighting the need to improve the judicial activity and promote a reflection on the postures adopted in the Judiciary of the Paraiba. This Search concluded by suggesting a new perspective to humanize the conciliatory attempt, taking the fundamentals of the Person Centered Approach to qualify and deploy the conciliation within the Judiciary proposing the conciliation a humanist